2017
DOI: 10.1155/2017/3726361
|View full text |Cite
|
Sign up to set email alerts
|

A New Model to Study Fatigue in Dental Implants Based on Probabilistic Finite Elements and Cumulative Damage Model

Abstract: The aim of this study was to predict the fatigue life of two different connections of a dental implant as in load transfer to bone. Two three-dimensional models were created and assembled. All models were subjected to a natural masticatory force of 118 N in the angle of 75° to the occlusal plane. All degrees of freedom in the inferior border of the cortical bone were restrained, and the mesial and distal borders of the end of the bone section were constrained. Fatigue material data and loads were assumed as ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
1
15
0
1
Order By: Relevance
“…Although these assumptions do not occur in clinical practice, they are common in finite element studies due to the challenges in establishing the properties of living tissues. These assumptions are consistent with other numerical studies [22,23,39]. In addition to these limitations, this work did not analyze the role of pterygoid implants as the goal was to study the biomechanical behavior of the plates.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Although these assumptions do not occur in clinical practice, they are common in finite element studies due to the challenges in establishing the properties of living tissues. These assumptions are consistent with other numerical studies [22,23,39]. In addition to these limitations, this work did not analyze the role of pterygoid implants as the goal was to study the biomechanical behavior of the plates.…”
Section: Discussionsupporting
confidence: 66%
“…In the last few decades, the finite element method (FEM) has become very popular in the field of biomechanics as it is a useful tool to numerically calculate aspects such as stresses and strains, and to evaluate the mechanical behavior of biomaterials and human tissues, considering the difficulty in making such an assessment in vivo [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These distortions reached the outer surface, indicating a structural failure of the implant. Previous research from Bordin et al [29], Freitas et al [27] and Prados-Privado et al [30] showed that the comparison between internal cone implants, external hexagon, and internal hexagon showed a clear advantage for internal conical implants in relation to the others, considering the fatigue of the material.…”
Section: Discussionmentioning
confidence: 90%
“…In this case, internal connection ( Figure 1b) allowed a better union between the implant and the abutment. Finally, morse taper connection (Figure 1c), which is another option for an internal connection, was introduced because of its improvement on screw loosening [14][15][16].…”
Section: Introductionmentioning
confidence: 99%